Study of the Habitat Preferences of Kima Clams in the Waters of Bama, Baluran National Park, Situbondo Regency, East Java - Aisyah, Assifa Dina (Aquatic Life Sciences, 2026)
Giant clams (Tridacnidae) play an important ecological role in coral reef ecosystems; however, their populations continue to decline due to habitat degradation and overexploitation. Despite increasing conservation efforts, site-specific information on habitat preference, particularly related to substrate composition, remains limited in many Indonesian reef systems, including Bama Waters, Baluran National Park. This study aimed to assess the community structure and substrate habitat preferences of giant clams in this area. Field surveys were conducted at four stations using belt transect and quadrat methods, complemented by underwater photo transect analysis for substrate characterization and measurement of key environmental parameters. Community structure was analyzed using density and the Shannon–Wiener diversity index, while habitat preference was evaluated using Ivlev’s electivity index. A total of three giant clam species were recorded with Tridacna crocea dominating with a density of 0.52 ind/ha. Diversity was categorized as low to moderate and varied spatially in relation to substrate composition. Stations with mixed substrates, particularly hard coral and rubble, supported higher diversity values. Electivity analysis revealed species-specific habitat preferences, with T. crocea favoring rocky substrates, T. maxima associated with hard coral and rubble, and T. squamosa showing weaker habitat specialization. These findings suggest that substrate composition plays an important role in shaping giant clam distribution in Bama Waters. This study provides site-specific ecological information that may support more effective conservation and management strategies for giant clams in coral reef ecosystems.